Risk Balancing of Cold Ischemic Time against Night Shift Surgery Possibly Reduces Rates of Reoperation and Perioperative Graft Loss. (19th January 2017) - Emmanouilidis, Nikos; Boeckler, Julius; Ringe, Bastian P.; Kaltenborn, Alexander; Lehner, Frank; Koch, Hans Friedrich; Klempnauer, Jürgen; Schrem, Harald
Abstract : Background. This retrospective cohort study evaluates the advantages of risk balancing between prolonged cold ischemic time (CIT) and late night surgery. Methods. 1262 deceased donor kidney transplantations were analyzed. Multivariable regression was used to determine odds ratios (ORs) for reoperation, graft loss, delayed graft function (DGF), and discharge on dialysis. CIT was categorized according to a forward stepwise pattern ≤1 h />1 h, ≤2 h />2 h, ≤3 h />3 h, …, ≤ nh /> nh . ORs for DGF were plotted against CIT and a nonlinear regression function with bestR 2 was identified. First and second derivative were then implemented into the curvature formulak ( x ) = f ′ ′ ( x ) / ( 1 + f ′ x 2 ) 3 / 2 to determine the point of highest CIT-mediated risk acceleration. Results. Surgery between 3 AM and 6 AM is an independent risk factor for reoperation and graft loss, whereas prolonged CIT is only relevant for DGF. CIT-mediated risk for DGF follows an exponential patternf x = A · ( 1 + k · e I · x ) with a cut-off for the highest risk increment at 23.5 hours. Conclusions. The risk of surgery at 3 AM–6 AM outweighs prolonged CIT when confined within 23.5 hours as determined by a new mathematical approach to calculate turning points of nonlinear time related risks. CIT is only relevant for the endpoint of DGF but had no impact on discharge on dialysis, reoperation, or graft loss.